Two Therapeutic Approaches to Creativity Motivation of Management Trainees:: An Experiment in Nigeria - Nwaneri, Ada (Journal of Comparative International Management, 2010)
The purpose of the study is to investigate the effect of problem solving and cognitive restructuring approaches in improving the creativity motivation of management trainees through enhancing their individual creative behaviour. A 3 x 2 factorial design was adopted in this study. The sample of study consisted of 102 subjects randomly drawn from a stratum of management trainees undergoing Masters Program in Business Administration in three Universities in Ibadan, Nigeria. Three validated instruments were used for data collection before and after therapy. Analysis of covariance and t – test statistics were used to test the generated hypotheses at 0.05 level of significance. The results obtained showed that both the creative problem-solving and cognitive restructuring techniques were effective in improving management trainees’ creative behaviour and consequently raising their level of creativity motivation. However, creative problem-solving technique was found to be significantly more effective than cognitive restructuring technique in raising subjects’ creativity motivation. The findings also indicated that the intervention strategies were effective in raising the creativity motivation of both Type A and Type B personality subjects. However, while problem-solving technique was more effective for Type B personality subjects, cognitive restructuring technique was found to have more effect in raising the level of creativity motivation of Type A subjects. Based on the outcome of the study, managers and researchers wishing to foster motivation for creativity in the organizations can do so, not only by paying attention to work environments that enhance creativity motivation, but also by trying to improve the creative behaviour of individuals at work using these or similar intervention measures.